A recombinant Mycobacterium smegmatis-based surface display system for developing the T cell-based COVID-19 vaccine - Ziyu Wen; Cuiting Fang; Xinglai Liu; Yan Liu; Minchao Li; Yue Yuan; Zirong Han; Congcong Wang; Tianyu Zhang; Caijun Sun (Taylor & Francis Group, 2023)
The immune escape mutations of SARS-CoV-2 variants emerged frequently, posing a new challenge to weaken the protective efficacy of current vaccines. Thus, the development of novel SARS-CoV-2 vaccines is of great significance for future epidemic prevention and control. We herein reported constructing the attenuated Mycobacterium smegmatis (M. smegmatis) as a bacterial surface display system to carry the spike (S) and nucleocapsid (N) of SARS-CoV-2. To mimic the native localization on the surface of viral particles, the S or N antigen was fused with truncated PE_PGRS33 protein, which is a transportation component onto the cell wall of Mycobacterium tuberculosis (M.tb). The sub-cellular fraction analysis demonstrated that S or N protein was exactly expressed onto the surface (cell wall) of the recombinant M. smegmatis. After the immunization of the M. smegmatis-based COVID-19 vaccine candidate in mice, S or N antigen-specific T cell immune responses were effectively elicited, and the subsets of central memory CD4+ T cells and CD8+ T cells were significantly induced. Further analysis showed that there were some potential cross-reactive CTL epitopes between SARS-CoV-2 and M.smegmatis. Overall, our data provided insights that M. smegmatis-based bacterial surface display system could be a suitable vector for developing T cell-based vaccines against SARS-CoV-2 and other infectious diseases.